Enhanced coordination interaction with multi-site binding ligands for efficient and stable perovskite solar cells - Riming Nie; Peikun Zhang; Jiaxing Gao; Cheng Wang; Weicun Chu; Luyao Li; Kaiyu Wang; Dongmin Qian; Fanrong Lin; Xuefeng Xia; Yong Wu; Lingfeng Chao; et al. (Nature Communications)
Abstract Conventional passivating ligands bind to perovskite surfaces through only a single active site, which not only creates a resistive barrier due to dense ligand packing but also restricts the enhancement of device stability. Here, we identify an antimony chloride-N,N-dimethyl selenourea complex, Sb(SU)2Cl3, as a multi-anchoring ligand to significantly enhance perovskite crystallinity, suppress defect formation, and dramatically improve moisture resistance and overall stability. As a result, we achieve a power conversion efficiency of 25.03% in fully air-processed perovskite solar cells fabricated using a two-step method—among the highest efficiencies reported for devices prepared under ambient conditions. Remarkably, unencapsulated cells exhibited linear extrapolated T 80 lifetimes of 23,325 h during dark shelf storage. Furthermore, these unencapsulated devices demonstrate exceptional thermal and operational stability, with T 80 lifetimes of 5,004 (at 85 °C) and 5,209 hours (under 1-sun illumination), respectively, ranking them among the most stable perovskite solar cells to date.